Mapping Indigenous Communal Lands : A Review of the Literature from a Cambodian Perspective - Adler, Daniel; Ironside, Jeremy; Ratanak, Mean (World Bank, Washington, DC, 2012)
The Cambodian Land Law (2001) provides indigenous ethnic minority groups with a right to register their traditional residential and agricultural lands under communal title. To date, however, this right has remained unrealized. While the government has been working on a pilot registration process in three villages and drafting implementing regulations under the land law, Cambodia's once remote highlands have become increasingly exposed to the forces of state and market. The result: indigenous communities are being transformed; livelihoods change; and land is subject to deforestation, sales and grants of government concessions for mining and agribusiness. The Royal Government has included in its policy documents a commitment to the 'interim protection' of indigenous lands prior to registration; however, to progress on this front has been limited. The review of the literature contained in this note is adapted from a study examining the potential of community mapping to serve as an interim protective measure.